Influence of silver nitrate on the mechanical properties of orthopedic bone cement and in vitro antibacterial activity - Osowski, Alini [UNESP]; Rahal, Sheila Canevese [UNESP]; Ribeiro, Celso Roberto; Campeiro, Luiz Donizete [UNESP]; Siqueira Silva, Jose Ivaldo de [UNESP]; Cassanego, Guilherme Rech [UNESP]; Gilio Gasparotto, Paulo Henrique (Univ Federal Goias, 2025)
This study aimed to evaluate the influence of silver nitrate (AgNO3) on the mechanical properties of polymethyl methacrylate (PMMA) bone cement by static testing and in vitro antibacterial activity. Two groups were formed: Group 1, control (n=10); and Group 2, cement with silver nitrate (n=10). In Group 1, the cement was prepared manually by mixing 20 g of PMMA powder with 10 ml of methyl methacrylate liquid. In Group 2, the cement was prepared as in Group 1; however, 0.25 g of silver nitrate was added to 20 g of PMMA powder. No statistical differences were observed for bending strength with (61.80 +/- 4.96 MPa) or without silver nitrate (60.20 +/- 5.88 MPa). Statistical differences were verified in the higher compressive strength for the control (78.60 +/- 3.20 MPa) compared to cement with silver nitrate specimens (74.20 +/- 1.61 MPa). Antimicrobial sensitivity testing showed no effect of cement with silver nitrate on Staphylococcus aureus, Streptococcus sp., Pseudomonas aeruginosa, and Escherichia coli. In conclusion, the concentration of silver nitrate did not change the mechanical properties of the PMMA bone cement in the bending test, but it had a negative effect in the compression testing. In addition, the product did not reduce the bacterial load in the in vitro test.
Keywords: polymethylmethacrylate; mechanical testing; sample; static testing